Impact of vehicle electrification on global supply chains and emission transfer - Yuya Nakamoto; Shohei Tokito; Minami Kito (Environmental Research Letters, 2023)
Numerous countries plan to promote increased levels of vehicle electrification. This study demonstrates that, when considering the life cycle of automobiles, higher levels of vehicle electrification over the next 30 years in Japan would generate higher carbon emissions, preventing the country from meeting carbon reduction and neutrality targets in 2030 and 2050, respectively. In 2020, 2030, and 2050, domestic emissions could decrease to 92.5, 72.9, and 49.6 Mt, respectively, while emission transfers to other countries could reach 12.1 Mt (11.5% of the global carbon footprint), 10.4 Mt (12.5%), and 8.7 Mt (14.9%). The results indicate that even if the widespread use of alternative fuel vehicles could reduce domestic emissions, such emissions might be transferred to foreign countries, and blanket promotion of automobile electrification should be avoided. Instead, governments and the automotive industry should take responsibility for global and whole life-cycle emissions of vehicles, not only domestic tank-to-wheel emissions. These results provide baseline information for use in the recommendation measures and international rules to be adopted by the automobile industry stakeholders and policymakers.